A cross-sectional survey study to assess attitudes towards research misconduct among the community of the American University in Cairo - Felaefel, Marwan Tarek (AUC Knowledge Fountain, 2015)
Background: Research misconduct is on the rise globally and it is jeopardizing scientific integrity by breaching the basis of responsible scientific conduct. Available data indicates rising levels of fabrication, falsification and plagiarism that are alarming despite the presence of guidelines in many of the high-income countries. High profile cases of misconduct in low and middle income countries are on the rise as well, yet data regarding the amount of misconduct taking place remain scarce. Objective: To assess investigators’ attitudes as well as the prevalence of research misconduct in an Egyptian University and identify possible factors that might account for our results. Methods: We performed a cross-sectional survey study at the American University in Cairo (AUC) that included undergraduates, post-graduates and faculty. The survey tool included the following sections: a) demographics, b) attitudes regarding the acceptability of certain practices in research conduct and c) frequency of observed and self-identified instances of scientific misconduct. The study was approved by the institutional review boards at AUC and at the University of Maryland, Baltimore. Data Analysis: We used descriptive analysis and a chi-square test for bivariate analysis. We entered data by the use of SPSS software. A p value of 0.05 was considered significant Results: We analyzed data from 191 participants 18 to 64 years of age. Of the respondents, 52.4% had received research ethics training. Regarding attitudes toward research misconduct: 1) 77.3% expressed concern about the occurrence of research misconduct, 2) 50.0% agreed that dishonesty and misrepresentation of data are common, 3) 64.5% regard pressures to publish to gain promotion is a major reason for engaging in misconduct. 4) 71.8% of participants confirmed their awareness of regulations that govern research involving humans, animals, or laboratory practices. Incidence of research misconduct observed at least once by participants included: plagiarism (43.8%), obtaining improper informed consents (34.6%), and eliminating data that contradicts one’s hypothesis (46.9%). Self-identified incidences for the same categories were 9.1%, 10.4%, and 26.0%; respectively. Conclusions: The results indicate that misconduct is related to level of education, work environment in addition to possible ineffectiveness of training. Results may be explained by a lack of understanding or awareness of the unethical nature of research misconducts. This study provides insights on the attitudes towards and prevalence of misconduct among researchers in the Egypt. Limitations: This study included self-reporting of self-identified practices, which could represent an underestimate of actual practice. Also, results from a single university may not be generalizable to other universities in Egypt and to other countries in the Middle East. Next steps: Data from other sites in Egypt and countries in the Middle-East are being gathered and will be pooled and analyzed with the data already collected. Further training in the responsible conduct of research is recommended. Further qualitative research (e.g., interview studies) is needed to further explore the reasons for our results.